Strengthening Africa’s resilience to Mpox: Preparedness and response initiatives of the Pasteur network - Delia D. Djuicy; Benjamin Selekon; Christian Malaka; Aboubacar Soumah; Edgar Adjogoua; Hervé Kadjo; Offianan A. Toure; Pierre Roques; Solène Grayo; Noël Tordo; Ousmane Faye; Abdourahmane Sow; et al. (Journal of Public Health in Africa)
n/a